Rock fracturing observation based on microseismic monitoring and borehole imaging: In situ investigation in a large underground cavern under high geostress. (August 2022) - Zhao, Jin-Shuai; Jiang, Quan; Lu, Jian-Fei; Chen, Bing-Rui; Pei, Shu-Feng; Wang, Zhi-Lin
Highlights: Integrated observation is used to capture the coseismic signal of rock fracturing. Fracture process of rock mass of the Baihetan Hydropower Station is studied. The microfracture, rupture and deformation of rock mass develop synergistically. Abstract: During the excavation of deep rock engineering projects under high geostress, the brittle failure of hard rock often occurs. To understand the excavation-induced fracturing process of the surrounding rock of a large underground powerhouse, in situ observation schemes have been proposed, including microseismic (MS) monitoring, imaging with a digital panoramic borehole camera, multipoint extensometer measurements and on-site surrounding rock failure investigation. First, a MS system is used to capture the microfractures inside the rock mass, revealing the potential high-risk failure regions. The spatial distribution of MS events shows that the excavation-induced MS events are progressively clustered in the upstream spandrel and downstream foot of the powerhouse, approximately parallel to the direction of the maximum principal stress. Second, the digital panoramic borehole camera and multipoint extensometer are arranged in the high-risk region to further reflect the rock mass fracture evolution and deformation response characteristics in the monitored section. The borehole camera observations of the top arch and sidewall indicate that the excavation unloading not only causes surrounding rock fracturing near the periphery of the cavern but also induces deep fracturing at a certain depth from the periphery of the cavern. From these comprehensive observation results, the mechanism of rock mass mechanical behaviour is clarified; that is, the macroscopic deformation or failure characteristics of the surrounding rock are directly related to the evolution of microfractures. The research results of this paper are valuable for the stability analysis and excavation optimization of similar underground caverns.